A logística reversa no gerenciamento de resíduos eletroeletrônicos: um desafio no BRASIL? - SOUZA, Luiciana Otoni de (2022)
Reverse logistics consists of an instrument of the National Solid Waste Policy according to which it enforces responsibility for the return of materials resulting from waste electrical and electronic equipment to consumers and producers, building a chain of management for the life cycle of electrical products And electronics. Brazil presents itself as the country, among the emerging ones, which produces the most such material. Such a panorama brings with it concerns about the toxic substances that make up Waste electrical and electronic equipment (WEEE). Therefore, this article seeks to highlight the current situation in Brazil and to make comparisons in other countries around the world in order to alert stakeholders interested in the need for adequate care in the management of electrical and electronic waste.